Clinical outcome in patients with peripherally‐sited atypical lipomatous tumours and dedifferentiated liposarcoma. (16th March 2015) - Kalimuthu, Sangeetha N; Tilley, Charles; Forbes, Georgina; Ye, Hongtao; Lehovsky, Katie; Pillay, Nischalan; Seddon, Beatrice M; O'Donnell, Paul; Pollock, Robin; Tirabosco, Roberto; Amary, M Fernanda; Flanagan, Adrienne M.
Abstract: The reported incidence of local recurrence of peripheral atypical lipomatous tumours is highly variable and is likely to reflect the different inclusion criteria of cases, and the design of previous studies. We aimed to study the incidence of local recurrence of 90 cases of atypical lipomatous tumours and an additional 18 cases of de novo dedifferentiated liposarcoma. All tumours were diagnosed on the basis of MDM2 amplification: all patients had their first treatment in the same specialist sarcoma unit and were followed for a minimum of 60 months. The tumours were diagnosed between 1997 and 2009 and followed until the end of 2014. Seventy cases (78%) of atypical lipomatous tumours were located in the thigh (mean size 195 mm on presentation). Eight atypical lipomatous tumours (8.9%) recurred locally, of which 50% recurred after 60 months. The only two tumours with intralesional excisions recurred. Seven of the eight recurrent tumours were detected by the patient by self‐examination. One case recurred a second time as a dedifferentiated liposarcoma. Seventeen per cent of the de novo dedifferentiated liposarcomas recurred within 60 months of presentation. Extending the study period revealed that atypical lipomatous tumour could recur up to 40 years after the first surgery. Furthermore, of 26 tumours that recurred in the extended study, 27% recurred more than once, and three of the seven that recurred more than once transformed into a dedifferentiated liposarcoma. We recommend that, following post‐operative wound care, patients with atypical lipomatous tumour are referred back to their general practitioner for follow up, but that in the event of a suspected recurrence they have rapid access back to the specialist unit using a 'supported discharge' scheme. In the event of an intralesional excision and if a lesion recurs, patients are followed in a specialist unit at regular intervals: whether MRI scanning is a valuable means of monitoring such patients is unclear and requires an evidence base